2007
DOI: 10.1002/macp.200600652
|View full text |Cite
|
Sign up to set email alerts
|

Carboxybetaine Polymer‐Protected Gold Nanoparticles: High Dispersion Stability and Resistance against Non‐Specific Adsorption of Proteins

Abstract: Abstract1‐Carboxy‐N,N‐dimethyl‐N‐(2′‐methacryloyloxyethyl)methanaminium inner salt (CMB) was polymerized by ATRP initiated with a disulfide difunctionalized by 2‐bromoisobutyryl groups. The disulfide‐carrying carboxybetaine polymer (DT‐PCMB) was used for the preparation of PCMB‐protected gold nanoparticles (PCMB‐AuNPs) obtained by the reduction of hydrogen tetrachloroaurate (HAuCl4) in the presence of the DT‐PCMB of different molecular weights at different molar ratios of DT‐PCMB and HAuCl4. The sizes of gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 81 publications
3
61
0
Order By: Relevance
“…Similar to the revolutionary changes brought to polyelectrolyte synthesis [106], polyzwitterions have equally profited from this development. RDRP techniques offer direct access to polymers bearing zwitterionic groups with previously unthinkable features, such as predefined molar masses and narrow molar mass distributions [163,[182][183][184][185][186][187][188][189] as well as well-defined functional end groups [61,166,182,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208]. Moreover, complex architectures, such as block copolymers [14,[46][47][48]166,167,169,173,187,, graft copolymers [164,213,237,[241][242]…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the revolutionary changes brought to polyelectrolyte synthesis [106], polyzwitterions have equally profited from this development. RDRP techniques offer direct access to polymers bearing zwitterionic groups with previously unthinkable features, such as predefined molar masses and narrow molar mass distributions [163,[182][183][184][185][186][187][188][189] as well as well-defined functional end groups [61,166,182,[190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208]. Moreover, complex architectures, such as block copolymers [14,[46][47][48]166,167,169,173,187,, graft copolymers [164,213,237,[241][242]…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
“…A particularly fertile aspect of the evolving RDRP methods for polyzwitterions has been the possibility to control "grafting-from" processes on surfaces [33,35,129,165,186,187,195,199,202,. This development has given rise to a wealth of activities aimed at producing thin, but dense tethered zwitterionic hydrogel films that control friction and adhesion, and may be above all, the fouling behavior of surfaces.…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
“…Our group has recently found by using localized surface plasmon resonance (LSPR) spectroscopy that a polymer brush of carboxybetaine was highly resistant to non-specific adsorption of proteins. [17,18] Other research groups also have reported that modification of solid surfaces with carboxybetaine polymers reduced protein adsorption and platelet adhesion. [19,20] However, the biocompatibility (in other words, anti-biofouling property) of ''carboxybetaine copolymers'' has not been evaluated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] The ATRP method has also been applied to the polymerization of various zwitterionic monomers. [2][3][4][5][6][38][39][40][41][42][43][44][45][46][47][48] Zwitterionic polymers have been designed to mimic phosphatidylcholine (lecithin) that is abundant in cell membranes, and their applicability to the biomedical field has extensively been investigated. For example, polymer films composed of butyl methacrylate (BMA) and zwitterionic monomers such as 2-methacryloyloxyethylphosphorylcholine (MPC, phosphobetaine), 3-sulfo-N,N-dimethyl-N-(3'-methacrylamidopropyl)propanaminium inner salt (SPB, sulfopropylbetaine with an amide form) and 1-carboxy-N,N-dimethyl-N-(2'-methacryloyloxyethyl)methanaminium inner salt [CMB, caboxymethylbetaine, Scheme1 (a)] were found to be highly biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39,65] In a recent study, it was reported that a CEB polymer grafted on a glass substrate highly resists against protein adsorption and cell adhesion. [2] In this report, a zwitterionic polymer brush-protected glass substrate was prepared by the ATRP of CMB from surfaceconfined initiating sites, and a resistance against non-specific adsorption of proteins to the surfaces of PCMB brush was examined.…”
Section: Introductionmentioning
confidence: 99%